Numerical Simulation of Oil Spill in the Arctic Ice-Covered Waters: Focusing on Different Ice Concentrations and Wave’s Impacts - Wei Li; Zhenpeng Dong; Wanying Zhao; Xiao Liang (Journal of Marine Science and Engineering, 2023)
The computational model was established to investigate the characteristics of oil spreading under arctic environments focusing on two aspects: ice concentrations and wave impacts. The ice field was constructed using the ice plates to compose three kinds of fixed arrays based on different ice concentrations of 90%, 60% and 0%. The wave was generated using the improved Jonswap spectrum method to control the focusing time, focusing location and focusing wave amplitude. The oil spreading’s movement was simulated and compared to the field experiment to verify the numerical model’s validity. The oil spill was trapped under the ice plates’ lower surface when the ice concentration was 60% or 90%, which had a spreading velocity slower than the non-ice water. The moving ice simulation was performed via the overset technique and coupled with the current, wind and wave. With ice drifting, the oil spreading was accelerated, leading to the presence of oil both on and under the ice surface. The ice was driven by the wave to affect the running details of the oil trajectory. These findings can be utilized for future oil spreading prediction when an oil spill accident occurs in the Arctic Ocean.